Value of Safety of Anticoagulant Therapy in Elderly Patient with Atrial Fibrillation and High Risk of Bleeding - N. M. Vorobyeva; O. N. Tkacheva (Столичная издательская компания, 2023)
The review article discusses  the safety issue of anticoagulant therapy in elderly patients with atrial fibrillation and high risk of bleeding.  An evidence base is presented demonstrating the high safety of rivaroxaban in patients over 80  years of age,  with a high risk of bleeding  and cardiovascular complications,  the presence of comorbid  pathology, geriatric syndromes  and chronic kidney disease (including in combination with anemia). The problem of low adherence to treatment in elderly patients and the possibility of solving it were separately considered.